Plan de negocios para la creación de un isp con vigilancia domiciliaria con cámaras ip - Arias Montero, Johanna E (2009)
In the present business plan is realized a study of market and financial feasibility for the implementation of a Internet Service Provider with home monitoring via IP cameras and wireless technology in the northern of the Guayaquil city , which provide surveillance home during the hours that the user or customer outside his home. The user can monitor activities through a Web portal or record the information on his/her PC. The purpose is to alleviate the concern of people who are responsible for children under 12 years or older people. The plan includes an analysis of financial viability and feasibility to detail the costs involved the creation and development of an ISP, the technical resource and logistics for the implementation of this service, projected income, with financial criteria and on a market survey, until the implementation of the project.